Odpowiedź :
Odpowiedź:
[tex]A.\ \ 2\cdot1\frac{1}{4}-\frac{1}{4}:9=2\cdot\frac{5}{4}-\frac{1}{4}\cdot\frac{1}{9}=\frac{10}{4}-\frac{1}{36}=\frac{90}{36}-\frac{1}{36}=\frac{89}{36}=2\frac{17}{36}\\\\\\B.\ \ 2\cdot(1\frac{1}{4}-\frac{1}{4}:9)=2\cdot(\frac{5}{4}-\frac{1}{4}\cdot\frac{1}{9})=2\cdot(\frac{5}{4}-\frac{1}{36})=2\cdot(\frac{45}{36}-\frac{1}{36})=2\cdot\frac{44}{36}=\\\\=2\cdot\frac{11}{9}=\frac{22}{9}=2\frac{4}{9}[/tex]
[tex]C.\ \ 2\cdot(1\frac{1}{4}-\frac{1}{4}):9=2\cdot1:9=2:9=\frac{2}{9}\\\\\\D.\ \ (2\cdot1\frac{1}{4}-\frac{1}{4}):9=(2\cdot\frac{5}{4}-\frac{1}{4}):9=(\frac{10}{4}-\frac{1}{4}):9=\frac{\not9}{4}\cdot\frac{1}{\not9}=\frac{1}{4}\\\\Odp.D[/tex]